"I like talking to people on the computer": Outcomes of a home-based intervention to develop social media skills in youth with disabilities living in rural communities. (May 2018) - Raghavendra, Parimala; Hutchinson, Claire; Grace, Emma; Wood, Denise; Newman, Lareen
Abstract: Purpose: To investigate the effectiveness of a home-based social media use intervention to enhance the social networks of rural youth with disabilities. Method: Participants were nine youth (mean age = 17.0 years) with disabilities from two rural Australian communities. The intervention consisted of providing appropriate assistive technology and social media training on individualised goals. Using mixed methods, quantitative (a single group pre-post) and qualitative (interviews with participants and their carers) measures were used to examine outcomes of training, individual experiences of the intervention, and changes to online social networks. Results: Participants increased their performance and satisfaction with performance on social media problem areas post-intervention; paired t -tests showed statistical significance at p <  .001. There was also a significant increase in the number of online communication partners; Wilcoxon Signed Ranks showed statistical significance at p <  .05. The interviews highlighted increased social participation, independence and improvements to literacy. Ongoing parental concerns regarding cyber safety and inappropriate online content were noted. Conclusions: The findings suggest that social media training is a feasible method for increasing social networks among rural-based youth with disabilities. To sustain ongoing benefits, parents need knowledge and training in integrating assistive technology and social media.